Drawing trees in a streaming model - Binucci, Carla; Zweig, Katharina A. (Information processing letters, 2012)
We pose a new visualization challenge, asking Graph Drawing algorithms to cope with the requirements of Streaming applications. In this model a source produces a graph one edge at a time. When an edge is produced, it is immediately drawn and its placement cannot be altered. The drawing has an image persistence, that controls the lifetime of edges. If the persistence is k, an edge remains in the drawing for the time spent by the source to generate k edges, and then it fades away. In this model we study the area requirement of planar straight-line grid drawings of trees and we assess the output quality of the presented algorithms by computing the competitive ratio with respect to the best known offline algorithms.
Gesehen am 10.08.2018